Growth and Formation Mechanism of Branched Carbon Nanotubes by Pyrolysis of Iron(II) Phthalocyanine - Wei, Qiong; Liu, Yunyun; Zhang, Lijie; Huang, Shaoming (Nano-Micro Letters, 2013)
In this letter, a route for synthesizing vertically aligned multi-walled carbon nanotubes (MWCNTs) with branched nanotubes in large area was reported. The branched MWCNTs up to about 30% can be generated by the pyrolysis of iron(II) phthalocyanine in presence of thiol under Ar/H2 at 800∼900°C. The growth mechanism of the branched nanotubes was proposed and the possible reason that thiol enhanced branched nanotubes growth is discussed. The as-prepared samples provide a suitable candidate to investigate the special electrical or thermal properties of CNTs with branched structures further.